Pengaruh Pembelajaran Matematika Terintegrasi Islam terhadap Motivasi Belajar Siswa - Yugita Rahmi; Cici Wahyuni; Hijriani Safitri; Azila Nur Aqsa; Akbar Nasrullah; Isnaniah; Imamuddin M. (Department of Master Program on Mathematics Education Faculty of Teacher Training and Education State Islamic Institute of Lhokseumawe, Indonesia, 2023)
Mathematics learning activities continue to evolve. One of these developments is the practice of learning mathematics that is integrated with Islam. This is inseparable from the goal that mathematics not only fosters intellectual values, but can also express spiritual values in students. The purpose of this study is to determine the effect of Islamic integrated mathematics learning on student learning motivation. This research uses the literature review method and the sample is journals that have been published from 2014-2023 totalling 49 articles. The results of this study found that: 1) The research trend of Islamic integrated mathematics learning in increasing student learning motivation from year to year is increasing, 2) The research subjects that are often used in research are many at the MA / SMA level, which is 40%, 3) The type of research used in the article is literature review and qualitative, 4) The effect of Islamic integrated mathematics learning on increasing student learning motivation is very good. Educators are expected to implement Islamic integrated learning in mathematics classes.